OAUNI photometry of ASASSN-16gq/AT2016cym - Pereyra, Antonio (2017)
We report optical photometry of Type Ia SN ASASSN-16gq/AT2016cym (ATel #9199, ATel #9219) on 2016-07-11 (UT) gathered with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging was performed with seeing ~1.7" and airmass = 1.3. Our measurements yielded: Date (UT) | filter | IT | mag 2016-07-11.085 | V | 1200s (60x20s) | 17.94 +/- 0.06 2016-07-11.106 | R | 0760s (38x20s) | 17.84 +/- 0.04 Field stars were used for the zero point calibration. Caution must be taken for contamination of edge-on Sc host galaxy (ESO 446-G023). Following FLWO/FAST classification (ATel #9219), our measurements are ~17 days after maximum. The OAUNI project is supported by UNI, TWAS, IGP and Cienciactiva (Convenio 102-2015 Fondecyt)."